Non‐Interpenetrated Single‐Crystal Covalent Organic Frameworks - Liang, Lin; Qiu, Yi; Wang, Wei David; Han, Jing; Luo, Yi; Yu, Wei; Yin, Guan‐Lin; Wang, Zhi‐Peng; Zhang, Lei; Ni, Jianwei; Niu, Jing; Sun, Junliang; et al. (Angewandte Chemie International Edition, 2020)
Growth of covalent organic frameworks (COFs) as single crystals is extremely challenging. Inaccessibility of open‐structured single‐crystal COFs prevents the exploration of structure‐oriented applications. Herein we report for the first time a non‐interpenetrated single‐crystal COF, LZU‐306, which possesses the open structure constructed exclusively via covalent assembly. With a high void volume of 80 %, LZU‐306 was applied to investigate the intrinsic dynamics of reticulated tetraphenylethylene (TPE) as the individual aggregation‐induced‐emission moiety. Solid‐state 2H NMR investigation has determined that the rotation of benzene rings in TPE, being the freest among the reported cases, is as fast as 1.0×104 Hz at 203 K to 1.5×107 Hz at 293 K. This research not only explores a new paradigm for single‐crystal growth of open frameworks, but also provides a unique matrix‐isolation platform to reticulate functional moieties into a well‐defined and isolated state. A 3D single‐crystal COF with a non‐interpenetrated structure was constructed for the first time. The highly open framework provides a unique matrix‐isolation platform to investigate the intrinsic dynamics of individual AIE moiety.